2022
DOI: 10.21037/jtd-22-1322
|View full text |Cite
|
Sign up to set email alerts
|

Qishen Yiqi dropping pills improve cardiomyocyte hypertrophy via the lncRNA TINCR/miR-193b-3p/RORA axis

Abstract: Background This study was designed to explore the therapeutic effect and mechanism of action of Qishen Yiqi dropping pills (QYDP) in chronic heart failure (CHF) via a long non-coding RNA (lncRNA)-microRNA (miRNA)-messenger RNA (mRNA) axis. Here, the mechanism of action of the lncRNA terminal differentiation-induced non-coding RNA (TINCR), miR-193b-3p, and RAR-related orphan receptor A (RORA) mRNA was analyzed in an angiotensin (Ang) II-induced H9C2 cardiomyocyte hypertrophy model treated with QYDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…MiR-193b-3p regulates cardiac necrosis and I/R injury Recent advances have revealed that miR-193b-3p participates in the regulation of pulmonary hypertension in heart failure[36], cardiac hypertrophy [37] and apoptotic pathway in myocardial I/R injury [38]. However, the role of miR-193b-3p in cardiac programmed necrosis has not been clari ed.…”
Section: Synaptotagmin-1 Is Suppressed By Mir-193b-3pmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-193b-3p regulates cardiac necrosis and I/R injury Recent advances have revealed that miR-193b-3p participates in the regulation of pulmonary hypertension in heart failure[36], cardiac hypertrophy [37] and apoptotic pathway in myocardial I/R injury [38]. However, the role of miR-193b-3p in cardiac programmed necrosis has not been clari ed.…”
Section: Synaptotagmin-1 Is Suppressed By Mir-193b-3pmentioning
confidence: 99%
“…Previous studies on the functions of miR-193b-3p were mainly focused on tumor [47,48], in ammation [49,50], and metabolism [36,51]. Recent advances have revealed that miR-193b-3p participates in the regulation of pulmonary hypertension in heart failure[36], cardiac hypertrophy [37] and the apoptotic pathway in myocardial ischemia/reperfusion injury [38]. However, the roles of miR-193b-3p in the cardiomyocyte necrotic death have not been explored.…”
Section: Synaptotagmin-1 Is Suppressed By Mir-193b-3pmentioning
confidence: 99%
“…Clinically, Zhang et al (2022) proved that it mainly treats symptoms of qi deficiency and blood stasis, such as chest tightness and chest pain, shortness of breath, and spontaneous sweating. Chen L, et al (2022) found that Qishen Yiqi dripping pills mainly play an auxiliary role in the treatment of patients with coronary heart disease, and Chen W, et al (2022) demonstrated that Qishen Yiqi dripping pills could be combined with Western medicine to treat diseases such as hypertension and angina.…”
Section: Introductionmentioning
confidence: 99%